Voces de mujeres : una aproximación a los imaginarios eróticos suscitados por el vudú en Krik? krak! de Edwidge Danticat (2019)
"This monograph consists of a literary analysis that studies how the erotic imaginaries uttered from a feminine place of enunciation in four stories contained in the anthology of short stories Krik? Krak! written by the Haitian author Edwidge Danticat are reconfigured as of voodoo as an element of fracture of their level of reality. In order to conduct the aforementioned analysis, the short stories on which the present study is based upon will be "Children of the Sea", "Nineteen Thirty-Seven2, "Night Women" and "Between the Pool and the Gardenias". Therefore, in first place the mechanisms of enunciation present in each one of the stories will be examined, hence, the narrator, the story space, the time and the levels of reality will be studied in connection with the chosen texts. Once the mechanisms of enunciation are established, throughout the second chapter of this work, its main topics will be adressed which means voodoo, fantastic literature and its subgenres..." -- Tomado del Formato de Documento de Grado.